"A loving man has a very huge responsibility": A mixed methods study of Malawian men's knowledge and beliefs about cervical cancer - Samuel Lewis; Corrina Moucheraud; Devon Schechinger; Misheck Mphande; Ben Allan Banda; Hitler Sigauke; Paul Kawale; Kathryn Dovel; Risa M. Hoffman (BMC, 2020)
Abstract Background In Malawi, numerous barriers may prevent women from accessing cervical cancer screening services - including social factors such as male partner involvement. We conducted surveys that included open- and closed-ended questions with married Malawian men to evaluate their knowledge and beliefs about cervical cancer. Methods HIV-positive adult (≥18 years) men (married or in a stable relationship) were recruited from an antiretroviral therapy clinic in Lilongwe, Malawi. Men were asked a series of survey questions to assess their knowledge about cervical cancer, experience with cervical cancer, their female partner's screening history, and their beliefs about gender norms and household decision-making. Following the survey, participants responded to a set of open-ended interview questions about cervical cancer screening, and men's role in prevention. Results One hundred-twenty men were enrolled with average age 44 years and 55% having completed secondary school or higher education. Despite only moderate knowledge about cervical cancer and screening (average assessment score of 62% correct), all men expressed support of cervical cancer screening, and most (86%) believed they should be involved in their female partner's decision to be screened. Over half (61%) of men said their female partner had previously been screened for cervical cancer, and this was positively correlated with the male respondent having more progressive gender norms around sexual practices. Some men expressed concerns about the screening process, namely the propriety of vaginal exams when performed by male clinicians, and whether the procedure was painful. Conclusions Male partners in Malawi want to be involved in decisions about cervical cancer screening, but have limited knowledge about screening, and hold rigid beliefs about gender norms that may affect their support for screening. Messaging campaigns addressing men's concerns may be instrumental in improving women's adoption of cervical cancer screening services in Malawi and similar settings.